2018
DOI: 10.1101/284141
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Altered Bile Acid Profile in Mild Cognitive Impairment and Alzheimer’s Disease: Relationship to Neuroimaging and CSF Biomarkers

Abstract: IntroductionBile acids (BAs) are the end products of cholesterol metabolism produced by human and gut microbiome co-metabolism. Recent evidence suggests gut microbiota influence pathological features of Alzheimer’s disease (AD) including neuroinflammation and amyloid-β deposition.MethodSerum levels of 20 primary and secondary BA metabolites from the AD Neuroimaging Initiative (n=1562) were measured using targeted metabolomic profiling. We assessed the association of BAs with the “A/T/N” (Amyloid, Tau and Neuro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
59
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 85 publications
8
59
1
Order By: Relevance
“…The ratio of primary conjugated and secondary bile acids with respect to cholic acid (CA) showed that deoxycholic acid (DCA), lithocholic acid (LCA), glycochenodeoxycholate (GCDCA), chenodeoxycholic acid (CDCA), taurodeoxycholic acid (TDCA), glycodeoxycholic acid (GDCA), ursodeoxycholic acid (UDCA), allolithocholate (alloLCA) and taurocholic acid (TCA) were higher in individuals with AD (CERAD score 1-3) compared to controls ( Figure 4). Similar results were reported in the serum metabolomics samples of AD and CN individuals 7,10 . Allo-cholic acid (ACA) is a steroid bile acid has been studied in the context of signaling mechanisms related to differentiation, proliferation or apoptosis of hepatocytes 30 .…”
Section: Cytotoxic Bile Acidssupporting
confidence: 88%
See 2 more Smart Citations
“…The ratio of primary conjugated and secondary bile acids with respect to cholic acid (CA) showed that deoxycholic acid (DCA), lithocholic acid (LCA), glycochenodeoxycholate (GCDCA), chenodeoxycholic acid (CDCA), taurodeoxycholic acid (TDCA), glycodeoxycholic acid (GDCA), ursodeoxycholic acid (UDCA), allolithocholate (alloLCA) and taurocholic acid (TCA) were higher in individuals with AD (CERAD score 1-3) compared to controls ( Figure 4). Similar results were reported in the serum metabolomics samples of AD and CN individuals 7,10 . Allo-cholic acid (ACA) is a steroid bile acid has been studied in the context of signaling mechanisms related to differentiation, proliferation or apoptosis of hepatocytes 30 .…”
Section: Cytotoxic Bile Acidssupporting
confidence: 88%
“…Bile acids are derived from cholesterol and their synthesis is regulated by complex feedback mechanisms 12,18 . Recent studies have identified bile acids in brain samples and linked them with cognitive decline in AD 7,10,19 . To understand the physiological role of bile acids in the brain of AD and CN individuals, we analyzed transcriptome data from post-mortem brain samples obtained from three independent cohorts and identified genes involved in the alternative bile acid pathway were expressed compared to the classical pathway in the brain.…”
Section: Role Of Bile Acids In Ad Pathophysiology and Use Of Genome-smentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 73 cortical thickness measures and 26 volume measures from different brain regions were extracted. 20 of them presented in Table 1 were found to be highly relevant to AD [27] and were used as quantitative traits in this analysis. analysis after performing standard quality control procedures for genetic markers and subjects.…”
Section: Mri Imaging Processingmentioning
confidence: 99%
“…This profiling technology has already been used to identify differential metabolites that can distinguish mild cognitive impairment (MCI) subjects who will develop AD from stable MCI 9 . Mounting evidence suggests that AD is closely accompanied with the abnormal bile acid (BA) metabolism [10][11][12][13] , free fatty acid (FFA) metabolism 14,15,26 , lipid metabolism 16,17 and neurotransmitter metabolism 18 . BAs are increasingly recognized as important metabolic signaling molecules that modulate lipid, glucose, and energy metabolism 19 .…”
Section: Introductionmentioning
confidence: 99%